The basic environmental economics of the circular economy - Peter Birch Sørensen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2017)
This paper sets up a Ramsey model with exhaustible natural resources to study the optimal recycling of polluting raw materials and household waste products. During the process of economic development it is optimal for the economy to go through an initial 'linear' phase with no recycling followed by a 'circular' phase where some materials and waste products are recycled to alleviate growing natural resource scarcity and environmental degradation. Ensuring the optimal degree of recycling in a market economy requires a Pigouvian tax on non-recycled raw materials combined with a subsidy to recycling of household waste and a tax on man-made wealth to internalize the environmental cost of capital accumulation.
Keywords: Q53; Q58; H21; 330; Circular economy; Linear economy; Optimal recycling; Hotelling rule; Pigouvian taxation; Environmental Kuznets Curve